Image of Poland and Polish Policy on Example of Selected Articles in German Medía during the Year 2017 - Trzcielińska-Polus, Aleksandra (Civilia, 2017)
The article presents the image of Poland and its politics, both foreign and internal, created by German press since early 2017 until August that same year. Newspapers issued in the Western and Easter part of the Federal Republic of Germany (mainly "Süddeutsche Zeitung" and "neues deutschland") were analyzed. The goal of this article is to answer the following question: what image of Poland is created in press in Germany and are there differences in this regard between liberal and left-wing media? Ten issues presented in the abovementioned newspapers were analyzed including, among others, the evaluation of the governing party PiS and the opposing parties, judicial reform, Polish migration policy, politics of memory, state of Polish-German relations.It was concluded that Poland is paid much more attention in German press than other Central and Eastern European states. The situation in Poland is very critically assessed in German media. In the critical appraisal of Poland and of the policy pursued by its government, no major differences in articles published in newspapers issued in Western and Eastern Germany were found.
Keywords: Poland; Polish politics; German media; PiS - governing party; Criticism